Editor's Column - Mladen Knezic (Electronics)
We are pleased to begin this year with four compelling new papers and an exciting milestone: for the first time, “Electronics” has been ranked as a Q2 journal by SCImago, achieving an SJR score of 0.4999 in 2024. Additionally, Scopus has ranked the journal in Q3 with a CiteScore of 1.6 (34th percentile) for 2024. These achievements reflect our ongoing commitment to enhancing the journal’s quality through rigorous publishing standards and adherence to best practices. We extend our gratitude to our authors, reviewers, and readers for their invaluable contributions to this progress. Looking ahead, we remain dedicated to further elevating impact and reputation of the journal. We invite researchers to submit their high-quality work and join us in advancing cutting-edge developments in different domains of electronics. In the first paper, entitled “Intelligent IoT Surveillance and Instantaneous Management,” Huang et al. proposed a fog-cloud-edge architecture enhanced with ResNetDL, a deep learning framework for industrial IoT. The system’s efficiency is evaluated using experimental results in which the system ensures 35 ms latency, 58 fps throughput, 210 mJ energy, 55% resource utilization, and 42 ms response time compared to other methods. The paper entitled “Wide-Band MIMO Antenna for Wireless Applications,” authored by Chouhan et al., brings a design of a compact four-port wide-band MIMO antenna. Operating at 2.16–4.3 GHz, the antenna achieves high isolation (more than 12 dB), low Envelop Correlation Coefficient (ECC) (less than 0.03), and minimal Specific Absorption Rate (SAR) (8.83 nW/kg near the human head for 1g), making it ideal for 5G and IoT devices. The octagonal geometry balances performance and manufacturability. In the third paper, entitled “Hardware Acceleration of Singular Spectral Analysis,” Varma et al. implement an FPGA-based Singular Spectral Analysis (SSA) accelerator for Nuclear Quadrupole Resonance (NQR) signal denoising. Their HLS-driven design achieves a 15.48x speedup over ARM Cortex-A9, with 32.4 dB Signal to Noise Ration (SNR) improvement. The last paper, entitled “CMOS Circuits Enhanced with Fe-MgO Tunnel Junctions,” by Chakraverty and Ramakrishnan, reports the influence of magnetic tunnel junctions on the electrical response of an operational amplifier (op-amp). The simulation results prove that the introduction of tunnel junction increases the bandwidth and the phase margin of the circuit. Furthermore, the open loop gain also improves with the addition of tunnel junction as compared to the baseline opamp simulation. These contributions reflect the journal’s commitment to bridging theory and practical innovation. Finally, I would like to extend gratitude to the authors and reviewers for their rigorous work and insights.